Static behavior of grouped large headed stud-UHPC shear connectors in composite structures. (15th December 2018) - Wang, Jingquan; Xu, Qizhi; Yao, Yiming; Qi, Jianan; Xiu, Hongliang
Abstract: Accelerated bridge construction (ABC) utilizing precast systems offers many benefits such as faster onsite construction and lower traffic impacts. Ultra-high performance concrete (UHPC) becomes an innovative solution that facilitates some types of ABC. This paper proposes a novel steel-UHPC composite system and large studs with diameter of 30 mm. Push-out tests are conducted to investigate the shear behavior of large studs embedded in UHPC and compared with normal strength concrete (NSC). A total of 6 single stud and 18 grouped studs specimens are used to investigate the effects of casting method, precast deck strength, infilling material strength and transverse reinforcement in the shear pocket. Test results showed that grouped stud effect in the UHPC specimen was insignificant. Ultimate strength of grouped stud in precast UHPC deck was 10% higher than that of NSC precast slab while interfacial slip of UHPC specimen was 17% lower. Noting that grouped large studs better match with UHPC since no visible crack was observed at failure in UHPC slab while NSC slab displayed a number of cracks. Finally, load-slip relationship for large grouped studs embedded in UHPC was proposed based on experimental results and comparisons between the test results of strength and codes predictions were made.